Understanding Political Will and Public Corruption in South Africa - Harris Maduku; Andrew Osehi; Enaifoghe - (Journal of Social and Development Sciences, 2018)
The objective of this paper is to extensively analyse if there is adequate political will to eradicate corruption in South Africa using existing literature. There has been a huge increase in the level of attention paid to corruption, measures to curb it as well as its socio-economic consequences. In South Africa, corruption has been at the focal point of development an obstruction and impediment of genuine improvement in the general public service delivery. South Africa’s public procurement system has been filled with corrupt practices, making the country to be one of the most degenerate on the continent of Africa. In the event that Africa is to be spared from this disease, the endemic presence of corrupt practices must be managed appropriately by the executive of the state. This paper addressed the concept of political will and normalized corruption in South Africa and proposed a route forward for the coveted change. We feel that corruption should be classified in the same category as crimes like treason, murder and rape and heavy sentences have to accompany corruption as a crime. A qualitative method was adopted in this study.